Successful sequential treatment with ofatumumab followed by efgartigimod for refractory autoimmune encephalitis with dual anti-NMDAR and anti-GFAP antibody positivity: first case report - Tu, Xin; Liu, Xi; Yang, Niao; Sun, Dong; Mei, Bin; Yan, Nao (Frontiers in Immunology, 2025)
Autoimmune encephalitis (AE) is a heterogeneous disorder mediated by autoantibodies targeting neuronal or glial antigens, with anti-NMDAR encephalitis being the most common subtype, while cases with dual antibody positivity remain exceedingly rare. Standard treatment involves stepwise immunotherapy, but refractory cases often require advanced therapies. This study presents the first reported case of dual anti-NMDAR and anti-GFAP antibody-positive refractory AE in a 24-year-old female who failed first-line treatments (steroids, IVIG) and ovarian teratoma resection. During disease progression, innovative sequential therapy with ofatumumab (OFA), a novel anti-CD20 monoclonal antibody, followed by efgartigimod, an FcRn antagonist, was employed to mitigate profound B-cell depletion risks. The patient exhibited significant clinical improvement, with reduced Modified Rankin Scale (mRS) scores from 5 to 1. OFA induced rapid B-cell depletion, while efgartigimod effectively cleared pathogenic IgG, demonstrating synergistic efficacy. Comparative analysis with literature cases highlighted the superiority of this sequential approach in balancing efficacy and safety.